Extracellular ATP and P2 purinergic signalling in the tumour microenvironment - Di Virgilio, Francesco; Sarti, Alba Clara; Falzoni, Simonetta; De Marchi, Elena; Adinolfi, Elena (Nature reviews. Cancer, 2018)
Modulation of the biochemical composition of the tumour microenvironment is a new frontier of cancer therapy. Several immunosuppressive mechanisms operate in the milieu of most tumours, a condition that makes antitumour immunity ineffective. One of the most potent immunosuppressive factors is adenosine, which is generated in the tumour microenvironment owing to degradation of extracellular ATP. Accruing evidence over the past few years shows that ATP is one of the major biochemical constituents of the tumour microenvironment, where it acts at P2 purinergic receptors expressed on both tumour and host cells. Stimulation of P2 receptors has different effects depending on the extracellular ATP concentration, the P2 receptor subtype engaged and the target cell type. Among P2 receptors, the P2X purinergic receptor 7 (P2X7R) subtype appears to be a main player in host-tumour cell interactions. Preclinical studies in several tumour models have shown that P2X7R targeting is potentially a very effective anticancer treatment, and many pharmaceutical companies have now developed potent and selective small molecule inhibitors of P2X7R. In this Review, we report on the multiple mechanisms by which extracellular ATP shapes the tumour microenvironment and how its stimulation of host and tumour cell P2 receptors contributes to determining tumour fate.